Diagnostic applications of health intelligence and surveillance systems - Yadav, Divakar 1976-; Bansal, Abhay; Bhatia, Madhulika 1984-; Hooda, Madhurima 1985-; Morato, Jorge 1967- (IGI Global, 2021)
"The book is a great reference about the various application and scientific work going on in this area of how AI is driving the Health sector and helping health practitioners to predict disease intensity using the latest technology"--